Significance of circular RNAs in regulating protein ubiquitination for malignant tumor progression - Zhong, Haidong; Li, Wei; Luo, Peiyue; Chen, Qi; Cheng, Le; Gan, Lifeng; Zhang, Fangtao; Lu, Yiran; Zheng, Liying; Qian, Biao (Frontiers in Immunology, 2025)
CircRNAs are an important class of non-coding RNAs, which are produced via back-splicing of exons and/or intron sequences of precursor mRNAs and generally cannot be translated into proteins as they do not bind to ribosomes. There is varying evidence supporting the claim that circRNAs are abnormally expressed in cancer and play a crucial role in cancer initiation and progression. Ubiquitin is a highly stable protein that can be conjugated to target proteins. The most crucial role of ubiquitination is to mediate the degradation of substrate proteins by the proteasome. An increasing amount of evidence indicates that circRNAs are involved in the precise degradation of proteins via the ubiquitin-proteasome system. This review systematically summarizes the intricate mechanisms by which circRNAs regulate target protein ubiquitination, modulate cancerous signaling pathways, and control tumorigenesis and tumor development. Although studies are continuously uncovering additional complex interactions between circRNAs and proteins, we believe that circRNAs are promising but challenging molecules that have the potential to facilitate precise cancer therapies in the future.